2020
DOI: 10.1029/2020jc016360
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Acoustic Inversion for Gas Flux Quantification—Application to a Methane Plume at Scanner Pockmark, Central North Sea

Abstract: The release of greenhouse gases from both natural and man‐made sites has been identified as a major cause of global climate change. Extensive work has addressed quantifying gas seeps in the terrestrial setting while little has been done to refine accurate methods for determining gas flux emerging through the seabed into the water column. This paper investigates large‐scale methane seepage from the Scanner Pockmark in the North Sea with a new methodology that integrates data from both multibeam and single‐beam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 73 publications
(182 reference statements)
0
16
0
Order By: Relevance
“…Gravity core observations of sediment fluidization features and disseminated iron sulphide, indicates active fluid flow directly beneath the pockmark. Evidence of methane-derived authigenic carbonates and gas ebullition at this site further demonstrates that active methane venting has persisted since 27 (Böttner et al, 2019;Li et al, 2020). As shown by controlled gas release experiments in weakly consolidated sediment (e.g., Roche et al, 2020), mature gas migration from an active, focused source may take place through stable open conduits.…”
Section: Depth Of S-wave Conversionmentioning
confidence: 62%
See 1 more Smart Citation
“…Gravity core observations of sediment fluidization features and disseminated iron sulphide, indicates active fluid flow directly beneath the pockmark. Evidence of methane-derived authigenic carbonates and gas ebullition at this site further demonstrates that active methane venting has persisted since 27 (Böttner et al, 2019;Li et al, 2020). As shown by controlled gas release experiments in weakly consolidated sediment (e.g., Roche et al, 2020), mature gas migration from an active, focused source may take place through stable open conduits.…”
Section: Depth Of S-wave Conversionmentioning
confidence: 62%
“…The Scanner pockmark is a composite feature comprising two overlapping seabed pockmarks (East and West Scanner), with a combined size of ∼900 m × 450 m wide and depth of 22 m, lying in ∼155 m water depth. Direct evidence for methane venting is provided by the water column imaging of Li et al (2020), who calculate a gas flux of 1.6 and 2.7 × 10 6 kg/year (272-456 l/min), as well as the presence of methane-derived authigenic carbonate (MDAC) recovered from within the pockmarks, which formed due to anaerobic oxidation of escaping methane (Judd and Hovland, 2009). The seismostratigraphy and lithostratigraphy hosting the Scanner pockmark complex comprises a ∼600 m-thick Quaternary sediment succession that has been described previously (Stoker et al, 2011;Böttner et al, 2019;Robinson et al, 2020), where it is sub-divided into five units, S1 to S5 (Figures 2, 3).…”
Section: Stratigraphy and Seismostratigraphic Frameworkmentioning
confidence: 99%
“…The workflow to estimate gas fluxes at the seep locations is illustrated in Figure 1. To estimate the BSD and density, we followed two approaches, one based on the normalized frequency response of the 18 and 38 kHz channels of the EK60 data, and one based on the non-normalized frequency response, similarly to the approach used by Li et al (2020).…”
Section: Estimation Of Gas Fluxesmentioning
confidence: 99%
“…To test the validity of the results, we analyse the dependence of the estimated methane fluxes on different BSD functions: we first parametrise the BSD by assuming log-normal and Weibull probability density functions (PDF), and then compare the inverted results (Figure 11). The choice of these PDFs was made based on published seep studies, which have suggested several distribution functions to describe bubble size data including normal (Römer et al, 2012), log-normal (Veloso et al, 2015;Wang et al, 2016;Li et al, 2020), and Weibull (Dey and Kundu, 2012).…”
Section: Constraints On Bubble Size Distributionsmentioning
confidence: 99%
See 1 more Smart Citation